Optically driven giant superbunching from a single perovskite quantum dot - Wang, Ziyu (2022)
Photon superbunching is a signature of a strong correlation between photons, which is a crucial resource needed in quantum communication and computation. As such, a superbunched photon source based on a material with high quantum efficiency, like cesium lead halide perovskite, is highly desirable. Utilizing the large dark–bright exciton splitting in CsPbBr3 quantum dot (QD), the authors achieve a superbunching with a large g(2)(0) ≈ 30 from an optically driven single CsPbBr3 QD emission at cryogenic temperature. The cascaded emission is identified as the cause of this superbunching by utilizing second-order cross-correlation measurement and exploring the excitation power and temperature dependence of the bunching level. The findings have immediate implications on the basic understanding of a single perovskite QD emission and its application as a quantum light source.